A Review of Dietary Intake of Acrylamide in Humans - Timmermann, Clara Amalie Gade (Toxics, 2021)
The dietary intake of acrylamide (AA) is a health concern, and food is being monitored worldwide, but the extent of AA exposure from the diet is uncertain. The aim of this review was to provide an overview of estimated dietary intake. We performed a PubMed search identifying studies that used dietary questionnaires and recalls to estimate total dietary AA intake. A total of 101 studies were included, corresponding to 68 original study populations from 26 countries. Questionnaires were used in 57 studies, dietary recalls were used in 33 studies, and 11 studies used both methods. The estimated median AA intake ranged from 0.02 to 1.53 μg/kg body weight/day between studies. Children were represented in 25 studies, and the body-weight-adjusted estimated AA intake was up to three times higher for children than adults. The majority of studies were from Europe (n = 65), Asia (n = 17), and the USA (n = 12). Studies from Asia generally estimated lower intakes than studies from Europe and the USA. Differences in methods undermine direct comparison across studies. The assessment of AA intake through dietary questionnaires and recalls has limitations. The integration of these methods with the analysis of validated biomarkers of exposure/internal dose would improve the accuracy of dietary AA intake exposure estimation. This overview shows that AA exposure is widespread and the large variation across and within populations shows a potential for reduced intake among those with the highest exposure.